Cosmology beyond BAO from the 3D distribution of the Lyman-α forest. Issue 4 (20th July 2021) - Cuceu, Andrei; Font-Ribera, Andreu; Joachimi, Benjamin; Nadathur, Seshadri
ABSTRACT: We propose a new method for fitting the full-shape of the Lyman-α (Ly α) forest 3D correlation function in order to measure the Alcock-Paczynski (AP) effect. Our method preserves the robustness of baryon acoustic oscillations (BAO) analyses, while also providing extra cosmological information from a broader range of scales. We compute idealized forecasts for the Dark Energy Spectroscopic Instrument (DESI) using the Ly α autocorrelation and its cross-correlation with quasars, and show how this type of analysis improves cosmological constraints. The DESI Ly α BAO analysis is expected to measure H ( z eff ) r d and D M ( z eff )/ r d with a precision of 0.9 per cent, where H is the Hubble parameter, r d is the comoving BAO scale, D M is the comoving angular diameter distance, and the effective redshift of the measurement is z eff ≃ 2.3. By fitting the AP parameter from the full shape of the two correlations, we show that we can obtain a precision of 0.5-0.6 per cent on each of H ( z eff ) r d and D M ( z eff )/ r d . Furthermore, we show that a joint full-shape analysis of the Ly α auto and cross-correlation with quasars can measure the linear growth rate times the amplitude of matter fluctuations in spheres of 8 h −1 Mpc, f σ8 ( z eff ). Such an analysis could provide the first ever measurement of f σ8 ( z eff ) at redshift z eff > 2. By combining this with the quasar autocorrelation in a joint analysis of the three high-redshift two-point correlation functions, we show that DESI could be able to measure f σ8 ( z eff ≃ 2.3) with a precision of 5-12 per cent, depending on the smallest scale fitted.